Systematization of previous research on exercises on the high bar - Paunovic, M.; Velickovic, S.; Vukašinovic, V. (Facta Universitatis: Series Physical Education and Sport, 2017)
The research was conducted with the aim to classify and systematize all the available studies that deal with exercises on the high bar. This research covered a total of 41 papers, spanning a period from 1990 to 2013. In terms of Code of points it includes as many as 144 elements that are performed and which should be performed at competitions. Of this number, only 18 elements were investigated (based on the collected papers), or 12.5%. This points to the fact that the research on exercises on the high bar, although conducted for a long period of time, is still in the beginning stages. Research of first (long hang swings and turns) and fifth (dismounts) specific requirements dominates. To a smaller extent, research on second (flight elements) specific requirements is represented, and the least attention is devoted to third and fourth requirements.